Corporate governance benefits of mutual fund cooperation - Rex Wang Renjie; Patrick Verwijmeren; Shuo Xia (Halle Institute for Economic Research (IWH), 2022)
Mutual fund families increasingly hold bonds and stocks from the same firm. We study the implications of such dual holdings for corporate governance and firm decision-making. We present evidence that dual ownership allows financially distressed firms to increase investments and to refinance by issuing bonds with lower yields and fewer restrictive covenants. As such, dual ownership reduces shareholder-creditor conflicts, especially when families encourage cooperation among their managers. Overall, our results suggest that mutual fund families internalize the shareholder-creditor agency conflicts of their portfolio companies, highlighting the positive governance externalities of intra-family cooperation.
urn:nbn:de:gbv:3:2-918853
Keywords: G23; G32; G34; 330; corporate governance; debt overhang; investment; mutual funds